Direct photoluminescence probing of ferromagnetism in monolayer two-dimensional CrBr3 - Zhang, Zhaowei (2020)
Atomically thin magnets are the key element to build up spintronics based on two-dimensional materials. The surface nature of two-dimensional ferromagnet opens up opportunities to improve the device performance efficiently. Here, we report the intrinsic ferromagnetism in atomically thin monolayer CrBr3, directly probed by polarization resolved magneto-photoluminescence. The spontaneous magnetization persists in monolayer CrBr3 with a Curie temperature of 34 K. The development of magnons by the thermal excitation is in line with the spin-wave theory. We attribute the layer-number-dependent hysteresis loops in thick layers to the magnetic domain structures. As a stable monolayer material in air, CrBr3 provides a convenient platform for fundamental physics and pushes the potential applications of the two-dimensional ferromagnetism.